Дослідження творчості Лесі Украінкі в Польщі: вибрані сторінки icтopii (3 нагоди 100-оі річниці письменниці) - Betko, Irena (Acta Polono-Ruthenica, 2018)
100-th anniversary of Lesia Ukrainka’s death (1871-1913), which is the great Ukrainian poet, writer and author of poetical drams, was celebrated on 1 August 2013. Her literary works are the objects of research in Polish during more than 120 years. Lesia Ukrainka is reprezented in polish histories of Ukrainian literature, which were written by Bohdan Łepki, Ryszard Łużny, Marian Jakóbiec, Bogusław Mucha, from 1930 to 2000. Florian Nieuważny, Stefan Kozak, Ewa Nikadem-Malinowska, Eulalia Papla, Sylwia Wójtowicz, Marta Reda, Agata Korycka and other had analyzed the chosen aspects of Lesia Ukrainka’s literary works on the second half of XX and on the beginning of XXI century.